STRATEGI PENGEMBANGAN STARTUP DENGAN MENGGUNAKAN PENDEKATAN LEAN CANVAS - Suryajaya, Dewa Made Bagus Bhima; Pradana, Bayu Ilham (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to identify the implementation of development strategy carried out by Lets Play Indonesia, a startup business, using the Lean Canvas approach. This study was conducted in response to the numerous collapsing initial driving startups and the worsening macroeconomic conditions during the last few years which disrupt the operation of educational startups. The data of this research was harvested from interviews, observations, and documentations. The results of the Lean Canvas analysis indicate that Lets Play Indonesia has not filled the key metrics part, so the product development strategy is required, in this case by adding an exercise evaluation feature. Furthermore, Lets Play Indonesia needs to add its customer segments by implementing market development strategy since its services have been well accepted. In terms of channels, Lets Play Indonesia needs to implement a more massive market penetration. Here information regarding the excellence of the solutions that they offer can be spread more widely using LinkedIn, company website, press release, and commerce journal. In general, Lets Play Indonesia needs to implement a focus strategy by applying differentiation and cost leadership strategies.